2018
DOI: 10.3390/genes9110526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Short-Term Fasting on The Rhythmic Expression of the Core Circadian Clock and Clock-Controlled Genes in Skeletal Muscle of Crucian Carp (Carassius auratus)

Abstract: The peripheral tissue pacemaker is responsive to light and other zeitgebers, especially food availability. Generally, the pacemaker can be reset and entrained independently of the central circadian structures. Studies involving clock-gene expressional patterns in fish peripheral tissues have attracted considerable attention. However, the rhythmic expression of clock genes in skeletal muscle has only scarcely been investigated. The present study was designed to investigate the core clock and functional gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Skeletal muscle circadian clocks respond to cyclic stimuli including feeding and activity through regulatory genes including CLOCK , ARNTL (aka BMAL1 ), and the period-family circadian regulator PER1 ( Schroder and Esser, 2013 ). Periods of fasting have been shown to alter the expression of key skeletal muscle circadian regulators and the cyclic expression of functional genes in fish skeletal muscle ( Wu et al, 2018 ). In the current study, key circadian rhythm related genes were upregulated during molt including ARNTL and PER1 ( Figure 2D ), and these genes are both tied to circadian regulation of mitochondrial lipid metabolism ( Ezagouri and Asher, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle circadian clocks respond to cyclic stimuli including feeding and activity through regulatory genes including CLOCK , ARNTL (aka BMAL1 ), and the period-family circadian regulator PER1 ( Schroder and Esser, 2013 ). Periods of fasting have been shown to alter the expression of key skeletal muscle circadian regulators and the cyclic expression of functional genes in fish skeletal muscle ( Wu et al, 2018 ). In the current study, key circadian rhythm related genes were upregulated during molt including ARNTL and PER1 ( Figure 2D ), and these genes are both tied to circadian regulation of mitochondrial lipid metabolism ( Ezagouri and Asher, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the circadian clock acts as an internal time-keeping mechanism to maintain homoeostasis in response to environment changings. Changes in expression of core clock genes in skeletal muscle after fasting have been reported in fish (33,34) . This study also showed that fasting significantly changed the rhythmic expression of circadian genes, for example, the acrophases of Clock were dramatically changed during 1, 5 and 7 d fasting.…”
Section: Discussionmentioning
confidence: 90%
“…The daily rhythmicity in relation to the expression of core circadian clock genes, KLF15 and Bcat2 , was assayed with Matlab 7.0. To perform a cosinor analysis, the formula ƒ(t) = M + Acos ( t/pi/12 –ϕ) was used, and the meanings of the letters in the formula refer to previous reports (34) . Significance of cosinor analysis was defined by the noise/signal of amplitude calculated from the ratio se(A)/A (hereafter referred as P -value).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations